Electrochemical inhomogeneities of steel in steel/copper alloy couple during galvanic corrosion in static and flowing seawater. Issue 4 (20th November 2018) - Li, Zhao; Liu, Jie; Zhang, Lunwu; Hou, Jian; Lu, Zhonghai; He, Jianxin; Zhang, Peiqing
Abstract : The electrochemical inhomogeneities of steel wires within a steel/copper alloy couple immersed in static and flowing seawater were studied by the wire beam electrode (WBE) technique, and the variations of the main anodic area of steel wires were discussed. It showed that the potential and current density distributions of steel wires in both static and flowing seawater were inhomogeneous while the electrochemical inhomogeneities of steel wires immersed in flowing seawater were significantly reduced. The main anodic area of steel wires immersed in static seawater moved from the steel wires at the edge of the WBE to other steel wires, and the main anodic area of steel wires immersed in flowing seawater moved from the steel wires adjacent to the steel/copper alloy interface to the steel wires further away. Polarity reversals of the single steel electrode can be found, but the reasons for the phenomena were different from each other. Abstract : The galvanic corrosion behaviors of a carbon steel/copper alloy couple exposed to static and flowing seawater have been studied. The electrochemical inhomogeneities of steel wires immersed in flowing seawater were reduced. There were the variations of main anodic area of steel wires and the polarity reversals of single steel electrode in the two seawater environments, but the reasons for the phenomena were different from each other.